Method for directly preparing formaldehyde-free lignin adhesive at low temperature
The method of directly preparing the anti-dehyde-free lignin adhesive by low temperature solves the problems of formaldehyde release of adhesives and non-renewable raw materials in wood composite materials, simplifies the process flow, reduces costs, and improves the bonding strength and environmental protection, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411551860.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-14
AI Technical Summary
The formaldehyde-based adhesive used in the production of wood composite materials in the prior art has formaldehyde release problems, and the raw materials are not renewable, and the cost is high; lignin adhesives have the disadvantages of long hot pressing time, high temperature, high acidity, and poor water resistance in applications. The preparation process is complicated and it is difficult to achieve large-scale industrial application.
The method of directly preparing a deldo-free lignin adhesive is adopted at low temperature. By treating lignin with mixed solution and curing agent in a one-pot method, the process flow is simplified, the cost is reduced, and the Improved glue strength.
It realizes direct preparation of hypoldrogenic lignin adhesives at low temperature, has high utilization rate of raw materials, low cost, and has no less than 0.7MPa in line with national standards, is suitable for industrial applications, and reduces the amount of glue applied and improves environmental protection.
Smart Images

Figure CN119307227A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and more specifically, relates to a method for directly preparing formaldehyde-free lignin adhesive at low temperature. Background Art
[0002] In the production of wood composite materials, the most commonly used adhesives are urea-formaldehyde resins, phenol-formaldehyde resins and melamine resin adhesives based on formaldehyde. Formaldehyde release is the biggest bottleneck that plagues resin synthesis and board production and application. In addition, the raw materials of the above three types of adhesives all come from non-renewable fossil resources. Today, the continuous rise in crude oil prices has increased the market cost of adhesives. The development and utilization of non-toxic, formaldehyde-free renewable raw materials to produce environmentally friendly adhesives has attracted much attention.
[0003] Lignin is the most widely available phenolic compound in nature. Its basic building blocks (syringyl, guaiacyl and p-hydroxybenzene) are similar to the phenol structure in phenolic resin adhesives, and have the potential to replace phenolic resin adhesives. The research on lignin adhesives can be traced back to the end of the 19th century, but it was not until the 1970s that production experiments began in Denmark, Switzerland, Finland and other countries. After the 1980s, the focus of related research has been on the chemical modification of lignin. There are two ways to use lignin in adhesives. One is to use lignin itself as an adhesive, but lignin itself as an adhesive has many disadvantages: long hot pressing time, high hot pressing temperature and acidity, the product is black and has very low physical and mechanical properties and low water resistance; the other is to mix lignin with other raw materials to modify the resin to make an adhesive.
[0004] Wastewater generated by the pulp and paper industry is the main source of industrial lignin. Currently, most of it is directly burned as fuel as a residue to provide power for factories, and only a small amount of industrial lignin is used. Due to the wide range of industrial lignin sources, complex structure, and low reactivity with formaldehyde, the amount of phenol substitution is small and the adhesive has disadvantages such as poor water resistance and low bonding strength. When preparing adhesives, it is necessary to further adopt modification methods to improve the reactivity of lignin to improve the phenol substitution rate and adhesive performance. However, there are disadvantages such as complex preparation process, high energy consumption, and large amount of chemicals. Currently, only partial substitution of phenol can be achieved. Therefore, using industrial lignin as raw material, developing a new green solvent system, and preparing environmentally friendly lignin adhesives by simple methods are important contents to achieve the replacement of traditional adhesives.
[0005] Patent CN106753231A discloses a lignin-based formaldehyde-free adhesive and its preparation method and use method. The preparation method is as follows: lignin and / or its derivatives, a catalyst and water are mixed to obtain a reduction system; the pH value of the reduction system is adjusted to 10-11, and then an activation treatment is performed, and the activation treatment product obtained includes an upper mixed liquid and a lower precipitate; the lower precipitate is heated with a protein-rich substance and water to obtain a lignin-based formaldehyde-free adhesive. However, the system requires multiple steps such as activation and heating using a catalyst, and the amount of glue applied is much higher than the actual application, which does not meet the requirements of industrial application.
[0006] Patent CN108611051A uses soybean powder and lignin as raw materials, activates soybean powder through surfactant combined with ultrasonic treatment, activates lignin through extrusion puffing combined with enzyme treatment, and then subjecting the activated lignin, activated soybean powder, cross-linking agent and water to supercritical fluid polymerization. The prepared biomass adhesive has good water resistance and environmental aging resistance, and is an environmentally friendly formaldehyde-free adhesive. However, the conditions for activating lignin and starch are relatively harsh, requiring higher pressure and temperature, and there are requirements for their particle size after activation.
[0007] Patent CN101412898 discloses a formaldehyde-free adhesive with a mixture of plant protein and lignin sulfonate as the base material, which obtains higher water resistance by modifying the protein itself. The adhesive has good water resistance and can meet the use standard of Class II glue. However, since the lignin used is not modified, most of it exists as filler and the added amount is relatively low.
[0008] Patent CN117467388A discloses a fully bio-based formaldehyde-free adhesive and a preparation method thereof. The preparation process is as follows: S1. The biomass extract is evaporated and concentrated, and then subjected to a dehydration reaction; S2. An appropriate amount of alkali is added to the reaction system, and the in-situ generated bio-based aldehyde substances and lignin undergo a cross-linking reaction under the catalytic action of sodium hydroxide to obtain a formaldehyde-free adhesive. However, both steps require the use of a catalyst and high-temperature heating conditions. Summary of the invention
[0009] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a method for directly preparing an aldehyde-free lignin adhesive at low temperature, which has a wide source of raw materials, a simple preparation method, low cost, and can achieve full utilization of the substrate. Another technical problem to be solved by the present invention is to provide an aldehyde-free lignin adhesive prepared by the above method, which meets national standards and is non-toxic and environmentally friendly.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0011] A method for directly preparing an aldehyde-free lignin adhesive at low temperature, wherein lignin is used as a raw material, a mixed solution and a curing agent are added to carry out a one-pot reaction, and the aldehyde-free lignin adhesive is prepared; wherein the bonding strength of the prepared aldehyde-free lignin adhesive is not less than 0.7MPa.
[0012] Preferably, the lignin is selected from any one of kraft lignin, organic solvent lignin and low eutectic solvent lignin. More preferably, the lignin is kraft lignin.
[0013] Preferably, the mixed solution is an ethanol aqueous solution containing a polyol, wherein the polyol is selected from any one of ethylene glycol, propylene glycol, butylene glycol, and pentanediol, and the concentration of the ethanol aqueous solution is 60 to 100 wt %. More preferably, the mixed solution is an ethanol aqueous solution containing propylene glycol, wherein the concentration of the ethanol aqueous solution is 75 wt %,
[0014] Preferably, the curing agent is selected from any one of ammonium chloride, ammonium sulfate, ammonium persulfate, ammonium phosphate, and diammonium hydrogen phosphate. More preferably, the curing agent is ammonium chloride.
[0015] The method for directly preparing the formaldehyde-free lignin adhesive at low temperature specifically comprises the following steps:
[0016] 1) mixing lignin with the mixed solution, heating and stirring to obtain a mixture;
[0017] 2) Add a curing agent to the mixture, and mix well to obtain a formaldehyde-free lignin adhesive.
[0018] Preferably, the mass ratio of the lignin to the mixed solution is 1:2 to 3. More preferably, the mass ratio of the lignin to the mixed solution is 1:2.
[0019] Preferably, after the lignin and the mixed solution are mixed, they are stirred and reacted at 60 to 100° C. for 10 to 180 minutes. More preferably, after the lignin and the mixed solution are mixed, they are stirred and reacted at 80° C. for 60 minutes.
[0020] Preferably, in the mixed solution, the mass ratio of the polyol to the ethanol aqueous solution is 1:1 to 6. More preferably, in the mixed solution, the mass ratio of the polyol to the 75 wt % ethanol aqueous solution is 1:2.
[0021] Preferably, the curing agent is added in an amount of 1 to 4 wt %, and more preferably, the curing agent is added in an amount of 2 wt %.
[0022] A formaldehyde-free lignin adhesive prepared by the preparation method, wherein the formaldehyde-free lignin adhesive is used to prepare plywood, and the amount of glue applied is 50-200 g / m 2, the hot pressing pressure is 1MPa, the hot pressing curing temperature is 150-180℃, and the hot pressing time is 10-30min.
[0023] A formaldehyde-free lignin adhesive prepared by the preparation method, wherein the formaldehyde-free lignin adhesive is used to prepare plywood, and the adhesive application amount is preferably 100 g / m 2 The hot pressing pressure is 1 MPa, the hot pressing curing temperature is preferably 180°C, and the hot pressing time is preferably 10 min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The lignin used in the present invention does not need to be modified or activated. The lignin can be directly heated and mixed with the mixed solution to form a lignin adhesive. The raw material source is wide, the preparation method is simple, the cost is low, the substrate can be fully utilized, and the large-scale preparation and industrial application of the lignin adhesive are promoted;
[0026] 2) The present invention can obtain the formaldehyde-free lignin adhesive by one-step dissolution at a relatively low temperature. The prepared lignin adhesive meets national standards and is non-toxic and environmentally friendly, and is an excellent lignin adhesive;
[0027] 3) The amount of adhesive applied to the lignin-based adhesive prepared by the present invention is lower than that of the currently commercially used lignin-based adhesive products, which has lower cost and is easier to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The dry strength / wet strength diagram of the adhesive plywood prepared in Examples 1-10, 12-14, 16-26. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] The preparation process of the kraft lignin used in the following examples is: it is obtained by acid precipitation from black liquor in a paper mill, and the pulping process uses poplar as raw material and adopts the sodium hydroxide / sodium sulfide method for pulping.
[0031] The preparation process of low eutectic solvent lignin is as follows: using poplar wood as raw material, pretreatment with choline chloride / p-toluenesulfonic acid (molar ratio 1:1) system (90°C, 60min, solid-liquid ratio of 1:10), filtering and separating the pretreatment liquid and the pretreatment substrate, diluting the pretreatment liquid with water in a volume ratio of 1:5, standing for 2h, and the precipitate is the low eutectic solvent lignin.
[0032] The preparation process of organic solvent lignin is as follows: wheat straw is used as raw material, pretreated with ethanol / water system (60v / v% ethanol, 160℃, 0.5h, solid-liquid ratio 1:10), the pretreated liquid and the pretreated substrate are separated by filtration, and the pretreated liquid is subjected to reduced pressure distillation to obtain organic solvent lignin.
[0033] Example 1
[0034] A method for directly preparing an aldehyde-free lignin adhesive at low temperature comprises the following steps:
[0035] (1) mixing ethylene glycol and 75 wt % ethanol aqueous solution in a mass ratio of 1:6 to obtain a mixed solution;
[0036] (2) mixing the kraft lignin and the mixed solution in a mass ratio of 1:3, heating and stirring at 80° C. for 60 min to obtain a mixture;
[0037] (3) Add ammonium chloride to the mixture at a mass ratio of 1 wt %, mix well to obtain a formaldehyde-free lignin adhesive. According to the test, the formaldehyde-free lignin adhesive prepared in Example 1 has a solid content of 25% and free formaldehyde of 0.
[0038] Example 2
[0039] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the lignin selected in step (2) is a low eutectic solvent lignin, and the remaining preparation methods and parameters are the same as those in Example 1 to obtain the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 2 has a solid content of 25% and free formaldehyde of 0.
[0040] Example 3
[0041] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the lignin selected in step (2) is organic solvent lignin, and the remaining preparation methods and parameters are the same as those in Example 1 to obtain the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 3 has a solid content of 25% and free formaldehyde of 0.
[0042] The formaldehyde-free lignin adhesives prepared in Examples 1 to 3 were prepared at 100 g / m 2The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 And as shown in Table 1.
[0043] Table 1 Bonding strength of the formaldehyde-free lignin adhesives prepared in Examples 1 to 3
[0044] Lignin Dry strength (MPa) Wet strength (MPa) Example 1 Kraft lignin 0.98 0.78 Example 2 Deep eutectic solvent lignin 0.95 0.76 Example 3 Organic solvent lignin 0.92 0.75
[0045] Depend on Figure 1 As shown in Table 1, under the same conditions, the dry strength and wet strength of kraft lignin prepared were higher than those of the other two lignins. In the subsequent examples, kraft lignin was selected as the research object.
[0046] Example 4
[0047] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the polyol selected in step (1) is propylene glycol, and the remaining preparation methods and parameters are the same as those in Example 1 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 4 has a solid content of 25% and free formaldehyde of 0.
[0048] Example 5
[0049] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the polyol selected in step (1) is butanediol, and the remaining preparation methods and parameters are the same as those in Example 1 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 5 has a solid content of 25% and free formaldehyde of 0.
[0050] Example 6
[0051] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the polyol selected in step (1) is pentanediol, and the remaining preparation methods and parameters are the same as those in Example 1 to obtain the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 6 has a solid content of 25% and free formaldehyde of 0.
[0052] The formaldehyde-free lignin adhesives prepared in Examples 4 to 6 were prepared at 100 g / m 2The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 And as shown in Table 2.
[0053] Table 2 Bonding strength of the formaldehyde-free lignin adhesives prepared in Examples 4 to 6
[0054] Polyols Dry strength (MPa) Wet strength (MPa) Example 4 Glycerol 1.01 0.80 Example 5 Butanediol 0.97 0.77 Example 6 Pentylene glycol 0.93 0.75
[0055] Depend on Figure 1 As shown in Table 2, under the same conditions, the dry strength and wet strength of the propylene glycol mixed solution prepared are higher than those of other polyols, and the propylene glycol mixed solution is selected in the subsequent examples.
[0056] Example 7
[0057] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the mass ratio of glycerol to ethanol aqueous solution in step (1) is 1:4, and the remaining preparation methods and parameters are the same as those in Example 1 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 7 has a solid content of 25% and free formaldehyde of 0.
[0058] Example 8
[0059] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the mass ratio of glycerol to ethanol aqueous solution in step (1) is 1:2, and the remaining preparation methods and parameters are the same as those in Example 1 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 8 has a solid content of 25% and free formaldehyde of 0.
[0060] Example 9
[0061] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the mass ratio of glycerol to ethanol aqueous solution in step (1) is 1:1, and the remaining preparation methods and parameters are the same as those in Example 1 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 9 has a solid content of 25% and free formaldehyde of 0.
[0062] The formaldehyde-free lignin adhesives prepared in Examples 7 to 9 were prepared at 100 g / m 2The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 And as shown in Table 3.
[0063] Table 3 Bonding strength of the formaldehyde-free lignin adhesives prepared in Examples 7 to 9
[0064] Mass ratio of glycerol to ethanol aqueous solution Dry strength (MPa) Wet strength (MPa) Example 7 1:4 1.04 0.81 Example 8 1:2 1.06 0.83 Example 9 1:1 1.01 0.76
[0065] Depend on Figure 1 As shown in Table 3, under the same conditions, when the mass ratio of glycerol to ethanol aqueous solution is 1:2, the dry strength and wet strength obtained are higher than those of other ratios, and the subsequent examples all select a mass ratio of 1:2.
[0066] Example 10
[0067] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the mass ratio of lignin to the mixed solution is 1:2, and the remaining preparation methods and parameters are the same as those in Example 8 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 10 has a solid content of 33% and free formaldehyde of 0.
[0068] Embodiment 11
[0069] When the formaldehyde-free lignin adhesive was directly prepared at low temperature, the mass ratio of lignin to the mixed solution was 1:1, and the remaining preparation methods and parameters were the same as in Example 8. The results showed that the lignin and the mixed solution could not be mixed uniformly. When the lignin content exceeded one third, it was difficult to form a uniform colloidal system.
[0070] The formaldehyde-free lignin adhesive prepared in Example 10 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1And as shown in Table 4.
[0071] Table 4 Bonding strength of the formaldehyde-free lignin adhesive prepared in Example 10
[0072] Mass ratio of lignin to mixed solution Dry strength (MPa) Wet strength (MPa) Example 10 1:2 1.08 0.85
[0073] Depend on Figure 1 As shown in Table 4, when the ratio of lignin to mixed solution is increased from 1:3 to 1:2, both the dry strength and wet strength of the plywood are improved, so 1:2 is subsequently selected as the preferred mass ratio.
[0074] Example 12
[0075] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the amount of ammonium chloride added is 2wt%, and the other preparation methods and parameters are the same as those in Example 10 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 12 has a solid content of 33% and free formaldehyde of 0.
[0076] Embodiment 13
[0077] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the amount of ammonium chloride added is 3wt%, and the other preparation methods and parameters are the same as those in Example 10 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 13 has a solid content of 33% and free formaldehyde of 0.
[0078] Embodiment 14
[0079] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the amount of ammonium chloride added is 4wt%, and the other preparation methods and parameters are the same as those in Example 10 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 14 has a solid content of 33% and free formaldehyde of 0.
[0080] The formaldehyde-free lignin adhesives prepared in Examples 12 to 14 were prepared at 100 g / m 2 The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 And as shown in Table 5.
[0081] Table 5 Bonding strength of the formaldehyde-free lignin adhesives prepared in Examples 12 to 14
[0082] The amount of ammonium chloride added Dry strength (MPa) Wet strength (MPa) Example 12 2wt% 1.10 0.87 Embodiment 13 3wt% 1.06 0.82 Embodiment 14 4wt% 0.85 0.63
[0083] Depend on Figure 1 As shown in Table 5, under the same conditions, when the addition amount of curing agent exceeds 3%, the dry strength and wet strength of plywood decrease significantly, so 2% is selected as the preferred addition amount.
[0084] Embodiment 15
[0085] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the concentration of the ethanol aqueous solution is 50%, and the remaining preparation methods and parameters are the same as those in Example 12. The results show that lignin and the mixed solution cannot be mixed evenly and it is difficult to form a colloidal system.
[0086] Example 16
[0087] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the concentration of the ethanol aqueous solution is 60%, and the remaining preparation methods and parameters are the same as those in Example 12 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 12 has a solid content of 33% and free formaldehyde of 0.
[0088] Embodiment 17
[0089] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the concentration of the ethanol aqueous solution is 80%, and the remaining preparation methods and parameters are the same as those in Example 12 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 12 has a solid content of 33% and free formaldehyde of 0.
[0090] Embodiment 18
[0091] When the formaldehyde-free lignin adhesive is directly prepared at low temperature, the concentration of the ethanol aqueous solution is 100%, and the remaining preparation methods and parameters are the same as those in Example 12 to prepare the formaldehyde-free lignin adhesive. After testing, the formaldehyde-free lignin adhesive prepared in Example 12 has a solid content of 33% and free formaldehyde of 0.
[0092] The formaldehyde-free lignin adhesives prepared in Examples 16 to 18 were prepared at 100 g / m 2 The three-layer plywood was obtained by applying and scraping on the poplar veneer, hot pressing at 1MPa and 150℃ for 30min, and standing in a ventilated place for 48h. Then, it was cut into the specified test pieces of length (100±1)mm and width (25±1)mm according to the test method of physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, taken out and cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured with a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 and as shown in Table 6.
[0093] Table 6 Bonding strength of formaldehyde-free lignin adhesives prepared in Examples 16 to 18
[0094]
[0095]
[0096] Depend on Figure 1 As shown in Table 6, under the same conditions, the strength of the plywood is the highest when the concentration of the ethanol aqueous solution is 75%, so 75% concentration is the preferred concentration.
[0097] Embodiment 19
[0098] The formaldehyde-free lignin adhesive prepared in Example 12 was heated to 50 g / m 2 Apply and scrape on poplar veneer to get three-layer plywood.
[0099] Embodiment 20
[0100] The formaldehyde-free lignin adhesive prepared in Example 12 was heated to 150 g / m 2 Apply and scrape on poplar veneer to get three-layer plywood.
[0101] Embodiment 21
[0102] The formaldehyde-free lignin adhesive prepared in Example 12 was heated to 200 g / m 2 Apply and scrape on poplar veneer to get three-layer plywood.
[0103] The three-layer plywood obtained in Examples 19 to 21 was hot-pressed at 1MPa and 150℃ for 30min, and allowed to stand in a ventilated place for 48h. Then, it was cut into test pieces of the specified length (100±1)mm and width (25±1)mm according to the test method for physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3h, and then cooled at room temperature for 10min to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured using a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are as follows: Figure 1 And as shown in Table 7.
[0104] Table 7 Bonding strength of formaldehyde-free lignin adhesives prepared in Examples 19 to 21
[0105] Scrape amount Dry strength (MPa) Wet strength (MPa) Embodiment 19 <![CDATA[50g / m 2 ]]> 0.89 0.61 Embodiment 20 <![CDATA[150g / m 2 ]]> 1.12 0.88 Embodiment 21 <![CDATA[200g / m 2 ]]> 1.13 0.89
[0106] Depend on Figure 1 As shown in Table 7, increasing the glue application amount to 100 g / m 2When the pressure is above 100 g / m, the adhesive seeps out obviously during the pressing process, and the strength of the plywood is limited. Considering the cost reduction, the glue application amount is preferably 100 g / m 2 .
[0107] Embodiment 22
[0108] The formaldehyde-free lignin adhesive prepared in Example 12 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by coating and scraping on poplar veneer, and hot pressing was carried out at 1MPa and 160℃ for 30min.
[0109] Embodiment 23
[0110] The formaldehyde-free lignin adhesive prepared in Example 12 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by coating and scraping on poplar veneer, and hot pressing was carried out at 1MPa and 170℃ for 30min.
[0111] Embodiment 24
[0112] The formaldehyde-free lignin adhesive prepared in Example 12 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by coating and scraping on poplar veneer, and hot pressing was carried out at 1MPa and 180℃ for 30min.
[0113] Embodiment 25
[0114] The formaldehyde-free lignin adhesive prepared in Example 12 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by coating and scraping on poplar veneer, and hot pressing was performed at 1MPa and 180℃ for 20min.
[0115] Embodiment 26
[0116] The formaldehyde-free lignin adhesive prepared in Example 12 was mixed at a pressure of 100 g / m 2 The three-layer plywood was obtained by coating and scraping on poplar veneer, and hot pressing was carried out at 1MPa and 180℃ for 10min.
[0117] After the plywood prepared in Examples 22 to 26 was left to stand in a ventilated place for 48 hours, it was cut into test pieces of the specified length (100±1) mm and width (25±1) mm according to the test method for physical and chemical properties of artificial boards and veneer artificial boards (GB / T 17657-1999). The test pieces were immersed in hot water at (63±3)℃ for 3 hours, and then cooled at room temperature for 10 minutes to obtain the treated test pieces. The bonding strength of the test pieces and the treated test pieces was measured using a universal testing machine. The untreated test pieces and the treated test pieces were tested 5 times respectively, and the average value was taken. The results are shown as follows: Figure 1 and as shown in Table 8.
[0118] Table 8 Bonding strength of the formaldehyde-free lignin adhesives prepared in Examples 22 to 26
[0119] Hot pressing conditions Dry strength (MPa) Wet strength (MPa) Embodiment 22 160℃,30min 1.15 0.90 Embodiment 23 170℃,30min 1.32 1.13 Embodiment 24 180℃,30min 1.69 1.38 Embodiment 25 180℃,20min 1.63 1.34 Embodiment 26 180℃,10min 1.61 1.31
[0120] Depend on Figure 1 As shown in Table 8, when the hot pressing temperature is gradually increased to 180°C, the strength of the plywood is significantly improved, but the surface color of the plywood gradually deepens. When the hot pressing time is shortened to 10 minutes, the color of the plywood does not change significantly, so the preferred hot pressing temperature and time are 180°C and 10 minutes.
[0121] Comparative Example 1
[0122] When preparing the formaldehyde-free lignin adhesive, only 75% ethanol aqueous solution is used as the mixed solution in step 1 of Example 12, and other conditions remain unchanged. Lignin cannot be mixed evenly in the ethanol aqueous solution and it is difficult to form a colloidal system.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for directly preparing formaldehyde-free lignin adhesive at low temperature, characterized in that: Lignin is used as a raw material, a mixed solution and a curing agent are added to carry out a one-pot reaction, and an aldehyde-free lignin adhesive is prepared; wherein the bonding strength of the prepared aldehyde-free lignin adhesive is not less than 0.7MPa.
2. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 1, characterized in that: The lignin is selected from any one of kraft lignin, organic solvent lignin and deep eutectic solvent lignin.
3. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 1, characterized in that: The mixed solution is an ethanol aqueous solution containing a polyol, wherein the polyol is selected from any one of ethylene glycol, propylene glycol, butanediol, and pentanediol, and the concentration of the ethanol aqueous solution is 60-100 wt%.
4. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 1, characterized in that: The curing agent is selected from any one of ammonium chloride, ammonium sulfate, ammonium persulfate, ammonium phosphate, and diammonium hydrogen phosphate.
5. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 1, characterized in that: The specific steps include: 1) mixing lignin with the mixed solution, heating and stirring to obtain a mixture; 2) Add a curing agent to the mixture, and mix well to obtain a formaldehyde-free lignin adhesive.
6. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 5, characterized in that: The mass ratio of the lignin to the mixed solution is 1:2-3.
7. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 5, characterized in that: After the lignin and the mixed solution are mixed, they are stirred and reacted at 60-100° C. for 10-180 minutes.
8. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 3, characterized in that: In the mixed solution, the mass ratio of the polyol to the ethanol aqueous solution is 1:1-6.
9. The method for directly preparing formaldehyde-free lignin adhesive at low temperature according to claim 1, characterized in that: The added amount of the curing agent is 1 to 4 wt%.
10. An aldehyde-free lignin adhesive prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The formaldehyde-free lignin adhesive is used to prepare plywood, and the amount of glue applied is 50-200 g / m 2 , the hot pressing pressure is 1MPa, the hot pressing curing temperature is 150-180℃, and the hot pressing time is 10-30min.
Citation Information
Patent Citations
Lignin-based aldehyde-free adhesive and preparation and application method thereof
CN106753231A
Biomass adhesive for wood and preparation method thereof
CN108611051A
Full-bio-based formaldehyde-free adhesive and preparation method thereof
CN117467388A